2021
DOI: 10.3390/rs13204155
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Crop Water Stress Assessment Using Remote Sensing

Abstract: Currently, the world is facing high competition and market risks in improving yield, crop illness, and crop water stress. This could potentially be addressed by technological advancements in the form of precision systems, improvements in production, and through ensuring the sustainability of development. In this context, remote-sensing systems are fully equipped to address the complex and technical assessment of crop production, security, and crop water stress in an easy and efficient way. They provide simple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 190 publications
0
29
0
Order By: Relevance
“…More capable techniques, such as quantifying leaf and stem water potential at midday [1], have been introduced; however, the methods are time consuming and destructive. Recently, the development of plant sensing equipment utilising remote sensing to assess environmental and plant physiological changes in a fast and nod-destructive manner has seen a significant leap in progress [2].…”
Section: Introductionmentioning
confidence: 99%
“…More capable techniques, such as quantifying leaf and stem water potential at midday [1], have been introduced; however, the methods are time consuming and destructive. Recently, the development of plant sensing equipment utilising remote sensing to assess environmental and plant physiological changes in a fast and nod-destructive manner has seen a significant leap in progress [2].…”
Section: Introductionmentioning
confidence: 99%
“…Another significant advancement is in the sand dune and bare areas; rising from only 4.1% of the total land area in 1990 to 4.6% in 10 years (2000), further increasing to 5.4% in another 10 years (2010) and surprisingly, 9% over the next 5 years (2010-2015). Elijah et al [34], also using satellite data analysis, reported a drastic increase in sand dunes in the study area between 2010-2013. Cumulatively, our results demonstrate that sand dunes and bare areas over the 25 years study period have more than doubled from the start year.…”
Section: Land Cover Changes From 1990 To 2015mentioning
confidence: 76%
“…Moreover, advanced vulnerability assessment and modelling techniques have facilitated the mapping and prediction of areas at the risk of desertification using complex desertification models, remote sensing data, climate records and other aridity indices [29][30][31][32][33]. Despite this, only a few scientific efforts exist in the Nigerian context, with respect to assessing and estimating desert areas using remote sensing and geographic information system (GIS) techniques and models [5,[33][34][35][36]. While the focus of most of these previous studies was on the assessment of the general time slices (i.e., intervals) of historic land cover change, and the measurement of the rate and impact of sand dune development, none evaluated the causes and drivers of desertification in the Nigerian context.…”
Section: Introductionmentioning
confidence: 99%
“…VRI has become technically feasible; however, crop water status mapping is necessary to combine irrigation amounts with site-specific crop water demands (Gobbo et al, 2019), although deciding when and where water should be applied has proven problematic (Chastain et al, 2016). An alternative that has been evolving for decades is remote sensing (RS), which can provide maps with sufficient details in a timely manner (Peschechera et al, 2019;Ahmad et al, 2021) and, in some situations, with constant data.…”
Section: Introductionmentioning
confidence: 99%